Structural and syntactic features of article titles about coronavirus - Shulzhenko, M. Yu (Vestnik of North-Eastern Federal University, 2024)
Over the past few years, articles regarding COVID-19 have remained pertinent in various media outlets, the internet and other communication platforms, which has ultimately resulted in the significance of the coronavirus topic not just in medical research, but also in the linguistic realm. Studying headlines of articles about coronavirus poses a challenge for researchers. The issue arises due to the significant role of journalism in influencing public opinion and the readership. Additionally, modern society's fascination with the coronavirus infection and the pandemic complicates the study further. The importance of this study is due to the newness of the subject matter, with limited coverage in scientific literature. The aim of this article is to examine the structural and semantic characteristics of article headings relating to the coronavirus. To achieve this goal, several tasks need to be accomplished. Firstly, it is necessary to identify and analyse the characteristics of the headline as part of the journalistic text, its various types and functions, and its consistency with the content of the article. Secondly, a study must be conducted on the structural and semantic features of the coronavirus-related article headlines. This includes determining the frequency of usage of different structural patterns of simple and complex sentences in both British and Russian publications, and examining the impact of these patterns on the readers' perception of the article's content. According to the research, it was concluded that the title of a publication serves a dual purpose as an independent unit and an essential component of the text. The title has various functions, including graphic-excretory, informative, nominative, and advertising-expressive. It is characterised by its brevity, nominativeness, and written fixity which contribute to its effectiveness.